Keratinolytic Activity of Artroderma and Chaetomium Species Isolated From Ujjain Soils - Dr Salil Singh (Research Parks Publishing LLC, 2022)
Twelve species of keratin decomposers isolated from 923 samples of feathers, nests and pellets of 90 species of free-living birds were clustered in 4